Inhibition of Tet1- and Tet2-mediated DNA demethylation promotes immunomodulation of periodontal ligament stem cells - Yu, Tingting (Cell Death Dis, 2019)
Periodontal ligament stem cells (PDLSCs) possess great potential for clinical treatment of immune diseases due to their extensive immunomodulatory properties. However, the underlying mechanisms that govern the immunomodulatory properties of mesenchymal stem cells (MSCs) are still not fully elucidated. Here, we show that member of the Ten-eleven translocation (Tet) family, a group of DNA demethylases, are capable of regulating PDLSC immunomodulatory functions. Tet1 and Tet2 deficiency enhance PDLSC-induced T cell apoptosis and ameliorate the disease phenotype in colitis mice. Mechanistically, we found that downregulation of Tet1 and Tet2 leads to hypermethylation of DKK-1 promoter, leading to the activation of WNT signaling pathway and therefore promoting Fas ligand (FasL) expression, which results in elevated immunomodulatory capacity of PDLSCs. These results reveal a previously unrecognized role of Tet1 and Tet2 in regulating immunomodulation of PDLSCs. This Tet/DKK-1/FasL cascade may serve as a promising target for enhancing PDLSC-based immune therapy.